Patient with H syndrome, cardiogenic shock, multiorgan infiltration, and digital ischemia - Laura Ventura-Espejo; Inés Gracia-Darder; Silvia Escribá-Bori; Eva Regina Amador-González; Ana Martín-Santiago; Jan Ramakers (BMC, 2021)
Abstract Background H syndrome (HS) is a rare autoinflammatory disease caused by a mutation in the solute carrier family 29, member 3 (SCL29A3) gene. It has a variable clinical presentation and little phenotype-genotype correlation. The pathognomonic sign of HS is cutaneous hyperpigmentation located mainly in the inner thighs and often accompanied by other systemic manifestations. Improvement after tocilizumab treatment has been reported in a few patients with HS. We report the first patient with HS who presented cardiogenic shock, multiorgan infiltration, and digital ischemia. Case presentation 8-year-old boy born to consanguineous parents of Moroccan origin who was admitted to the intensive care unit during the Coronavirus Disease-2019 (COVID-19) pandemic with tachypnoea, tachycardia, and oliguria. Echocardiography showed dilated cardiomyopathy and severe systolic dysfunction compatible with cardiogenic shock. Additionally, he presented with multiple organ dysfunction syndrome. SARS-CoV-2 polymerase chain reaction (PCR) and antibody detection by chromatographic immunoassay were negative. A previously ordered gene panel for pre-existing sensorineural hearing loss showed a pathological mutation in the SCL29A3 gene compatible with H syndrome. Computed tomography scan revealed extensive alveolar infiltrates in the lungs and multiple poor defined hypodense lesions in liver, spleen, and kidneys; adenopathy; and cardiomegaly with left ventricle subendocardial nodules. Invasive mechanical ventilation, broad antibiotic and antifungal coverage showed no significant response. Therefore, Tocilizumab as compassionate use together with pulsed intravenous methylprednisolone was initiated. Improvement was impressive leading to normalization of inflammation markers, liver and kidney function, and stabilising heart function. Two weeks later, he was discharged and has been clinically well since then on two weekly administration of Tocilizumab. Conclusions We report the most severe disease course produced by HS described so far in the literature. Our patient's manifestations included uncommon, new complications such as acute heart failure with severe systolic dysfunction, multi-organ cell infiltrate, and digital ischemia. Most of the clinical symptoms of our patient could have been explained by SARS-CoV-2, demonstrating the importance of a detailed differential diagnosis to ensure optimal treatment. Although the mechanism of autoinflammation of HS remains uncertain, the good response of our patient to Tocilizumab makes a case for the important role of IL-6 in this syndrome and for considering Tocilizumab as a first-line treatment, at least in severely affected patients.